Enhancing EFL students’ descriptive writing through the four-square method: A quasi-experimental study - Hermi Zaswita; Hesti Leviana Sari; Gulzhaina Kuralbayevna Kassymova (Researcher and Lecturer Society, 2026)
This study investigates the effectiveness of the Four-Square Writing Method (FSWM) in enhancing junior high school students’ ability to write descriptive texts. The FSWM is a structured graphic organizer strategy that helps students organize their ideas during the prewriting stage. A quasi-experimental design was employed, involving two groups of eighth-grade students: the experimental group received instruction using FSWM, while the control group was taught using conventional methods. Data were collected through pre-tests and post-tests to assess students’ writing performance. The results revealed a significant improvement in the experimental group, particularly in organizing ideas, maintaining coherence, and enriching vocabulary. Statistical analysis using an independent samples t-test via SPSS version 26 showed a significance value of 0.026 (p < 0.05) and a t-value of 12.146, exceeding the critical value of 1.713. These findings confirm that FSWM has a statistically significant impact on students’ writing skills and is therefore recommended as an effective strategy in English language instruction, especially for teaching descriptive texts.